Risk for Incident Heart Failure: A Subject‐Level Meta‐Analysis From the Heart "OMics" in AGEing (HOMAGE) Study. Issue 5 (2nd May 2017) - Jacobs, Lotte; Efremov, Ljupcho; Ferreira, João Pedro; Thijs, Lutgarde; Yang, Wen‐Yi; Zhang, Zhen‐Yu; Latini, Roberto; Masson, Serge; Agabiti, Nera; Sever, Peter; Delles, Christian; Sattar, Naveed; et al.
Abstract : Background: To address the need for personalized prevention, we conducted a subject‐level meta‐analysis within the framework of the Heart "OMics" in AGEing (HOMAGE) study to develop a risk prediction model for heart failure (HF) based on routinely available clinical measurements. Methods and Results: Three studies with elderly persons (Health Aging and Body Composition [Health ABC], Valutazione della PREvalenza di DIsfunzione Cardiaca asinTOmatica e di scompenso cardiaco [PREDICTOR], and Prospective Study of Pravastatin in the Elderly at Risk [PROSPER]) were included to develop the HF risk function, while a fourth study (Anglo‐Scandinavian Cardiac Outcomes Trial [ASCOT]) was used as a validation cohort. Time‐to‐event analysis was conducted using the Cox proportional hazard model. Incident HF was defined as HF hospitalization. The Cox regression model was evaluated for its discriminatory performance (area under the receiver operating characteristic curve) and calibration (Grønnesby‐Borgan χ 2 statistic). During a follow‐up of 3.5 years, 470 of 10 236 elderly persons (mean age, 74.5 years; 51.3% women) developed HF. Higher age, BMI, systolic blood pressure, heart rate, serum creatinine, smoking, diabetes mellitus, history of coronary artery disease, and use of antihypertensive medication were associated with increased HF risk. The area under the receiver operating characteristic curve of the model was 0.71, with a good calibration (χ 2 7.9, P =0.54). A web‐based calculator was developed to allow easy calculations of the HF risk. Conclusions: Simple measurements allow reliable estimation of the short‐term HF risk in populations and patients. The risk model may aid in risk stratification and future HF prevention strategies.